2c-6=4c+4

Simple and best practice solution for 2c-6=4c+4 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2c-6=4c+4 equation:


Simplifying
2c + -6 = 4c + 4

Reorder the terms:
-6 + 2c = 4c + 4

Reorder the terms:
-6 + 2c = 4 + 4c

Solving
-6 + 2c = 4 + 4c

Solving for variable 'c'.

Move all terms containing c to the left, all other terms to the right.

Add '-4c' to each side of the equation.
-6 + 2c + -4c = 4 + 4c + -4c

Combine like terms: 2c + -4c = -2c
-6 + -2c = 4 + 4c + -4c

Combine like terms: 4c + -4c = 0
-6 + -2c = 4 + 0
-6 + -2c = 4

Add '6' to each side of the equation.
-6 + 6 + -2c = 4 + 6

Combine like terms: -6 + 6 = 0
0 + -2c = 4 + 6
-2c = 4 + 6

Combine like terms: 4 + 6 = 10
-2c = 10

Divide each side by '-2'.
c = -5

Simplifying
c = -5

See similar equations:

| x-(-8)=-32 | | 4v+2-2(-8v-1)=2(v-3) | | X(.75)=3 | | -2+2x=-3+7x | | 45=24(-7X) | | 45=24-7X | | 2=-z/8+13 | | 55-2x=10-7x | | 32-4x=8(-5x-5) | | 24-16x=-12x | | 5p-5=30 | | 2x-9-6x=-7x+5x | | 2x+5=-44-5x | | 6x+9=9x+6 | | =v^2+2v-8 | | -2p-36=-4(-6+8p) | | -4.2=-0.84(m+4) | | -8w+14=0 | | 7y=9x+6 | | x(x-3)=x^2+6x+8 | | 8x-(6x-3)=17 | | 84=-7+7(a+5) | | 1/3(b-3)=6 | | -4v-1=0 | | p^2q^2=36 | | -4*6+6y=-24 | | -5p+20=25 | | 3x^4*2w^4x^5*8w=x | | 1(b-3)=6 | | 3y-12+63=180 | | 2x-(-15)=27-4x | | x/7-22=-1 |

Equations solver categories